Red sage a Chinese Plant: A Review of Phytochemical and Pharmacological Studies: Red sage a Chinese Plant: A Review of Phytochemical and Pharmacological Studies - Mittal, Abhilasha (International Journal of Pharmaceutical & Biological Archive, 2018)
Salvia splendens Linn. (Family: Lamiaceae), commonly known â€œRed sageâ€ or â€œScarlet sage,â€ has been used in the different traditional system of medicines for various ailments since ancient times. S. splendens grows throughout in Brazil and many other Asian countries such as India and China. This article aims to provide a comprehensive review of the phytochemical and pharmacological aspects of S. splendens. In traditional medicine, it has been used in the treatment of dressing of wounds and also applied to itchy skin by the leaves of the plant, roots are mainly used for cold and cough, and seeds are mainly used for emetic, dysentery, hemorrhoids, and colic disorders. It also used for the treatment of diabetes, hematemesis, leukoderma, pruritis, intestinal disorder and as antipyretics, analgesic, and laxative. The fruits, stem roots, and leaves of this plant contain a variety of biologically active compounds such as anthraquinones, flavonoids, flavon-3-ol derivatives, alkaloid, glycosides, tannin, saponin, terpenoids, reducing sugar, and steroids those have various medicinal properties. The leaves stem and roots extract shows various activities such as antipyretic, anti-inflammatory, antioxidant, antidiabetic, hypolipidemic, hepatoprotective, antimicrobial, antitumor, and antiulcer.